2007
DOI: 10.1534/genetics.107.076133
|View full text |Cite
|
Sign up to set email alerts
|

Cdc15 Is Required for Spore Morphogenesis Independently of Cdc14 in Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae exit from mitosis requires the Cdc14 phosphatase to reverse CDK-mediated phosphorylation. Cdc14 is released from the nucleolus by the Cdc14 early anaphase release (FEAR) and mitotic exit network (MEN) pathways. In meiosis, the FEAR pathway is essential for exit from anaphase I. The MEN component Cdc15 is required for the formation of mature spores. To analyze the role of Cdc15 during sporulation, a conditional mutant in which CDC15 expression was controlled by the CLB2 promoter was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 62 publications
11
47
0
Order By: Relevance
“…How DBF-2 may affect the function of N. crassa mating type loci and interacting genes/gene products has yet to be elucidated. The fact that CDC15 (a DBF2-interacting protein in S. cerevisiae) is required for meiosis II exit, as well as for spore morphogenesis (44), suggests that DBF2 may be linked with sexual reproduction in yeasts as well.…”
Section: Discussionmentioning
confidence: 99%
“…How DBF-2 may affect the function of N. crassa mating type loci and interacting genes/gene products has yet to be elucidated. The fact that CDC15 (a DBF2-interacting protein in S. cerevisiae) is required for meiosis II exit, as well as for spore morphogenesis (44), suggests that DBF2 may be linked with sexual reproduction in yeasts as well.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of the budding yeast CDC15 (homologous to cdc7 in fission yeast), mutants of which result in defects in the disassembly of anaphase II spindles and of the meiotic outer plaque of SPBs, leading to a sporulation defect similar to that described in SIN mutants; that is, the inability of forespore membranes to properly engulf haploid nuclei (Pablo-Hernando et al, 2007). Interestingly, the function of Cdc15 in sporulation seems to be independent of MEN and Cdc14 functions in meiotic divisions.…”
Section: Fig 9 Sid2mentioning
confidence: 94%
“…Blast searches failed to reveal the existence of a meiosisspecific homologue. However, a role for Dbf2 and/or Dbf20 in sporulation cannot be ruled out, because some MEN components have been shown to play a role in spore morphogenesis (Gordon et al, 2006;Kamieniecki et al, 2005;Pablo-Hernando et al, 2007). Dbf20 expression peaks later than Dbf2 during meiosis, suggesting that Dbf20 could be a better candidate to perform a role in sporulation than Dbf2 (Chu et al, 1998).…”
Section: Slk1: a Meiotic Sid2 Paraloguementioning
confidence: 99%
“…Interestingly, the phenotype of spo4Δ cells is similar to that of S. cerevisiae cells depleted for Cdc15. The MEN (mitotic exit network pathway) component Cdc15 is a protein kinase required for the formation of mature spores and for proper spindle disassembly after meiosis II 70 . Finally, it has been shown that cells expressing non-degradable cyclin B have prolonged anaphase B 50 .…”
Section: Discussionmentioning
confidence: 99%